Inside Back Cover: Differentiation between Single‐ and Double‐Stranded DNA through Local Capacitance Measurements (ChemElectroChem 6/2016). Issue 6 (13th May 2016) - Estrada‐Vargas, Arturo; Jambrec, Daliborka; Kayran, Yasin Ugur; Kuznetsov, Volodymyr; Schuhmann, Wolfgang
Abstract : The Inside Back Cover picture shows a Au wafer divided into two regions—a single‐ and a double‐stranded DNA region. By using scanning electrochemical impedance microscopy (SEIM) the single‐ and double‐stranded DNA regions can be differentiated through their local capacitance values in a simple, fast, and label‐free way. More information can be found in the Communication by W. Schuhmann and co‐workers onpage 855 in Issue 6, 2016 (DOI:10.1002/celc.201600075 ).